Childhood guttate psoriasis: an updated review - Alexander KC Leung; Benjamin Barankin; Joseph M Lam; Kin Fon Leong (BioExcel Publishing Ltd, 2023)
Background: Guttate psoriasis is common and affects 0.5-2% of individuals in the paediatric age group. This review aims to familiarize physicians with the clinical manifestations, evaluation, diagnosis and proper management of guttate psoriasis. Methods: A search was conducted in July 2023 in PubMed Clinical Queries using the key term "guttate psoriasis". The search strategy included all observational studies, clinical trials and reviews published within the past 10 years. The information retrieved from the search was used in the compilation of the present article. Results: Guttate psoriasis typically presents with an abrupt onset of numerous, small, scattered, tear-drop-shaped, scaly, erythematous, pruritic papules and plaques. Sites of predilection include the trunk and proximal extremities. There may be a history of preceding streptococcal infection. Koebner phenomenon is characteristic. Guttate psoriasis may spontaneously remit within 3-4 months with no residual scarring, may intermittently recur and, in 40-50% of cases, may persist and progress to chronic plaque psoriasis. Given the possibility for spontaneous remission within several months, active treatment may not be necessary except for cosmetic purposes or because of pruritus. On the other hand, given the high rates of persistence of guttate psoriasis and progression to chronic plaque psoriasis, some authors suggest active treatment of this condition. Conclusion: Various treatment options are available for guttate psoriasis. Triggering and exacerbating factors should be avoided if possible. Topical corticosteroids alone or in combination with other topical agents (e.g. tazarotene and vitamin D analogues) are the most rapid and efficient treatment for guttate psoriasis and are therefore the first-line treatment for mild cases. Other topical therapies include vitamin D analogues, calcineurin inhibitors, anthralin, coal tar and tazarotene. Ultraviolet phototherapy is the first-line therapy for moderate- to-severe guttate psoriasis, as it is more practical than topical therapy when treating widespread or numerous small lesions. Systemic immunosuppressive and immunomodulatory therapies (e.g. methotrexate, cyclosporine, retinoids, fumaric acid esters and biologics) may be considered for patients with moderate-to-severe guttate psoriasis who fail to respond to phototherapy and topical therapies.